In Silico Elucidation of the Molecular Recognition of Phenol Derivative Compounds and Hippuryl-histidyl-leucine as an Artificial Substrate with the Experimental Target: Angiotensin-converting Enzyme - Vázquez-Valaldez, Víctor H.; Hernández S, Manuel Alejandro; Cedillo, Ivonne Carrillo; Velázquez Sanchez, Ana María; Guevara, Mildred Sauce; Castañares, Rafael López; Ángeles, Enrique (Letters in Drug Design & Discovery, 2020)
Background: An elucidation study was carried out to evaluate 19 different methylthiomorpholine, methylmorpholine and piperidine compounds as possible inhibitors of the Angiotensin Converter Enzyme (ACE) using as a positive blank: Captopril, drug used as an antihypertensive agent and known for its biological effect over ACE. Also, the interaction using Hippuryl-histidyl-leucine (HHL) as an artificial substrate was simulated. Methods: The study was made using the Molecular Operating Environment (MOE), SYBYL and Gaussian software. Results: All the molecular recognition process was performed under the conditions reported for such interaction, in order to emulate the experimental parameters as close as is possible to a real system. Conclusion: After the calculations the best candidates for the ACE inhibition were determined.
Keywords: angiotensin converting enzyme